The Influence of High Performance Work System, Burnout on Intention to Leave with Mentoring as a Moderating Variable - Winarko, Bagus Arif Dwi; Sawitri, Hunik Sri Runing (International Journal of Scientific Research and Management (IJSRM), 2024)
Introduction: The Covid-2019 pandemic has had a negative impact on burnout and at the same time employee job satisfaction has become a benchmark for intentions to leave. Challenges in human resource management for health workers are experiencing very rapid changes which result in demand for nursing staff, community socio-economic conditions, declining family health status, and increasing public awareness. HPWS as a tool for identifying employee productivity with comprehensive training/mentoring contributes to new performance challenges. Fatigue and stopping work is a threat to companies. The aim of this research is to analyze the role of HPWS on intention to leave (ITL) with mentoring as a moderator and burnout as a mediator.Method : Quantitative research method with survey method using primary data in the form of questionnaires distributed to health workers who handle Covid-19 at private hospitals in Kab. Ponorogo. The sampling technique used simple random sampling with a sample size of 162 people. Hypothesis testing using Structural Equation Modeling (SEM)-PLS analysis with WarpPLS 7.0.Results : The research results show that HPWS has an influence on burnout and through mentoring moderation, HPWS has an influence on intention to leave, job satisfaction influences ITL with a significant difference (p